ChemInform Abstract: Microwaves and Aqueous Solvents Promote the Reaction of Poorly Nucleophilic Anilines with a Zincke Salt. Issue 34 (4th August 2016) - Zeghbib, Narimane; Thelliere, Paul; Rivard, Michael; Martens, Thierry
Abstract: The reaction tolerates a wide range of functional groups and delivers the arylpyridinium chloride products in generally high yields.